Noah’s Ark and the Flood in Judaism and Islam: A Bi-optic Perspective of Salvation and Sacred Space - Spoelstra, Joshua Joel (Scriptura, 2023)
This article analyses Noah’s ark and the flood events from the sacred texts and traditions of Judaism and Islam in an integrative manner. After juxtaposing the Flood Narrative in the Tanakh and the Noahic sūrahs of the Qur’an, key cognate lexemes are examined and their ideological trajectories traced. It is argued, particularly, that, in addition to the evident message of salvation in the Flood texts and traditions, there is a discernible ideological motif of sacred space in both religions, specifically the ark of Noah equivalent to or associated with a temple structure. Further, the Noah’s ark tradition seeps into various ancillary religious practices, both in various eras of Judaism and in Sunnism and Shiism. Thus, the convergences and divergences between Judaism and Islam, the Hebrew Bible and Qur’an concerning the reception history of a common patriarch (Noah) and shared spaces (ark, temple/mosque) is richly variegated from a bi-optic hermeneutical perspective.